Minimalizing Non-point Source Pollution Using a Cooperative Ion-Selective Electrode System for Estimating Nitrate Nitrogen in Soil - Su, Rui; Wu, Junfeng; Hu, Jiandong; Ma, Liuzheng; Ahmed, Shakeel; Zhang, Yanyan; Abdulraheem, Mukhtar Iderawumi; Birech, Zephania; Li, Linze; Li, Can; Wei, Wentao (Frontiers in Plant Science, 2022)
Nitrate nitrogen in soil is one of the important nutrients for growing crops. During the period of precipitation or irrigation, an excessive of nitrate nitrogen readily causes its leaching or runoff from the soil surface to rivers due to the inaccurate fertilization and water management, leading to non-point source pollution. In general, the measurement of the nitrate nitrogen relies upon lab-based absorbance, which is often time-consuming, therefore not suitable for the rapid measurements in field directly. Ion selective electrodes (ISE) support the possibility of nitrate nitrogen measurement by measuring the nitrate ions in soil quickly and accurately due to the high water solubility and mobility of nitrate ions. However, such method suffers from a complicated calibration to remove the influences caused by both temperature and other ions in the measured solution, thus limiting field use. Here, a kind of all-solid ISEs system combined with a temperature sensor and a pH electrode is proposed to automatically measure the concentrations of the nitrate nitrogen. In this study, a soil water content calibration function was established, which significantly reduces a relative error (RE) by 13.09%. The experimental results showed that the stabilization time of this electrode system was less than 15 s with a slope of 51.63 mV/decade in the linear range of 10-5-10-2.2 mol/L. Both the limit of detection of 0.5 ppm of the nitrate nitrogen and a relative standard deviation of less than 3% were obtained together with the recovery rate of 90%-110%. Compared with the UV-Vis spectroscopy method, the correlation coefficient (R2) of 0.9952 was obtained. The performances of this all-solid ISEs system are satisfied for measuring the nitrate nitrogen in field.